Nickel-catalyzed Suzuki cross-coupling reaction of alkyl triaryl phosphonium salts. (6th April 2023) - Zhu, Meiqi; Yu, Wen; Zhong, Qin; Cui, Benqiang; Cao, Changsheng; Shi, Yanhui
Abstract: The Suzuki cross-coupling reaction of triphenyl quaternary phosphonium triflates with boronic acids was reported. The reaction was catalyzed by Ni(COD)2 without additional ligand, using Cs2 CO3 as the base in toluene, and various biphenyls were synthesized in medium to excellent yields. This protocol has a wide adaptability to boronic acids, and many functional groups are tolerated. The method is scalable and could be performed on the gram scale. The regioselective arylation of differently substituted phenyl phosphonium triflates was observed at the side of electron-deficient phenyl group. Graphical abstract: Image 1